Factors affecting adherence to antiretroviral therapy in Andhra Pradesh, India - Raju, Bonu Naga; Anusuya, Ganesh Shanmugasundaram; Hari Lakshmi, V.; Johnson, Casper; Radhakrishnan, Ezhil; Ravi, Rama; Ramesh, Ronaki; Mohan Rao, Mangavalli Jagan (International Journal Of Community Medicine And Public Health, 2019)
Background: An important factor to effectiveness of ART is good adherence to treatment. This study aims to investigate the adherence levels to ART among people living with HIV (PLHIV) attending a Government ART centre in Anakapalli, Andhra Pradesh, India. Methods: A cross sectional study was done among 1000 adult PLHIV receiving ART. Out of nearly 4500 patients on ART we selected 1000 patients by simple random sampling technique. The average of adherence for a period of 2 years and socio demographic details were taken from the patients treatment card. Chi square test was performed to find out significant difference between the socio-demographic variables and adherence level < 95%. Results: Out of 1000 patients, 53.9% were male. 42.2% were in age group 31 to 40 years. 50.1 % had adherence >95%. Major factors influencing poor adherence were: decrease in weight (OR=18.65, p=0.000); decrease in CD4 counts (OR=20.12, p=0.000), presence of opportunistic infections (OR=12.67, p=0.000), WHO stage 3 and 4 illness (OR=6.50, p=0.000), travel distance to ART >50 kilometres (OR=1.94, p=0.000), smoker (OR=1.82, p=0.000),being illiterate (OR=1.72, p=0.000), and alcohol consumption (OR=1.58, p=0.001). Conclusions: Careful monitoring of weight, CD4 counts and opportunistic infections can help to identify poor adherence early.